Grundtvigs syn på Jens Møllers »bidrag til en oversættelsestheorie med nærmest hensyn til de bibelske skrifter« - Albeck, Gustav (Grundtvig-Studier, 1957)
Grundtvigs View of Jens Møllers “Contribution to a Theory of Translation, with Particular Reference to the Biblical Writings”. By Gustav Albeck. In his periodical, “Theologisk Bibliothek” (“The Theological Library”), Jens Møller, Professor of Theology at the University of Copenhagen, published an essay in 1811 with the title “Contribution to a Theory of Translation with Particular Reference to the Biblical Writings”. Møller, who was influenced by the aesthetic theories of the closing decades of the eighteenth century, and who combined a wide-ranging interest in literature and aesthetic theories with a thorough acquaintance with his University subject, introduced his essay with a series of reflections on the problems of translation in relation to profane literature (especially Classical poetry); and in it he made himself the spokesman for a theory which a german scholar, Griesbach, had already advanced thirty years earlier — namely that every country ought to have at least three different types of translations of the Scriptures: 1) A Bible for public use in the Church, “a sort of Protestant Vulgate”, whose principle should be “the highest degree of accuracy”. 2) A bible which, without losing its characteristic features as an ancient text, “could be read as an original work” — by “cultivated” readers — and in which the principle of translation should be “the middle way” between freedom on the one hand and beeing bound to the literal wording of the original on the other, and which should be characterised by “purity of language”. 3) An “elucidatory translation” for the common people and unpractised readers, which would almost be a paraphrase, “though without falling into the prolixity and wearisome tone of a paraphrase”. With regard to the last two groups Møller discussed the advisability of producing metrical translations of the poetical portions of the Old Testament — this suggestion being based on the view that “the reader’s aesthetic enjoyment is considerably increased when the nobler material is clad in a more beautiful form.” In a letter to Jens Møller on April 6th, 1813, Grundtvig mentions that he had intended (in 1811 or 1812) to publish his opinion of Møllers theory of translation, but had refrained from doing so because he feared that Møller would “interpret in a wrong sense”. A couple of finds in the great Grundtvig-Archives in the Royal Library prove that Grundtvig (presumably early in 1812) really had given written form to his objections against Møller’s theory of translation. Some sheets in fasc. 153 and 182 together make up a complete whole and are published here for the first time. Grundtvig expresses his opposition to Møller’s rather superficial and contradictory comments on the general problems of translation and strongly criticizes Møller for his belief (derived from Griesbach) in the advisability of having three different translations of the Bible. “Of translations (of the Bible) each country in a Christian age can have only one in the strictest sense of the word; that is to say, just as one must be authorised in the Church, that one must also have the confidence of all the unlearned, whether they be high or low, cultivated or ignorant”. His argument against Møller gives expression, not only to the indignation aroused in a Christian theologian by any attempt to profane the sacred songs of the Bible, but also to a poet’s professional dislike for poetic dilettantism.